The hand-reversal illusion revisited - Hong, Sang Wook; Xu, Linda; Kang, Min-Suk; Tong, Frank (Frontiers in Integrative Neuroscience, 2012)
The hand-reversal illusion is a visuomotor illusion that is commonly seen in children’s play. When participants attempt to lift a designated finger while their hands are cross-folded, they are likely to erroneously lift the matched finger of the other hand; however, such errors are rare when subjects close their eyes. Based on the fact that the illusion disappears without visual input, researchers previously concluded that the illusion depends upon visual and proprioceptive conflict (Van Riper, 1935). Here, we reevaluated this visual-proprioceptive conflict hypothesis by obtaining reaction time measurements because, in the original study, subjects might have relied on a strategy of responding more slowly to minimize making errors. We found that the impairment due to cross-folding one’s hand persisted in the absence of the visual input, as evidenced by delayed response times. Further, we found that such impairment occurred when the fingers of only one hand were tested, indicating that the impairment was not due to left-right confusions of the hands during tactile identification or response selection. Based on these results, we suggest that the illusion is not solely due to the conflict between visual and proprioceptive information. Instead, we propose that the unusual configuration itself that involves a reversal of the left and right hands in external space also contributes to the impaired motor response.